2008
DOI: 10.1590/s0103-84782008000100042
|View full text |Cite
|
Sign up to set email alerts
|

Superação da dormência de sementes de Schinopsis brasiliensis

Abstract: RESUMO Schinopsis brasiliensis (pre-drying).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
0
0
2
Order By: Relevance
“…After each storage period, half of the diaspores were scarifi ed, while the other remained intact. The diaspores were manually scarifi ed with 80-grit sand paper in the region near the micropyle (ALVES et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After each storage period, half of the diaspores were scarifi ed, while the other remained intact. The diaspores were manually scarifi ed with 80-grit sand paper in the region near the micropyle (ALVES et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…This layer increases seed longevity by preventing germination under favorable conditions as a survival strategy (SANTOS et al, 2018). Alves et al (2007) stated that mechanical scarifi cation was the most used procedure for overcoming dormancy of S. brasiliensis diaspores. In contrast, Oliveira and Oliveira (2008) found that the best way to obtain more regular, rapid, and complete germination of the diaspores consisted of removing the epicarp and mesocarp to eliminate germination inhibitors, pre-dryingduring storage for 25 to 30 days to cause cracks in the endocarp and sowing in moist sand to soften the endocarp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roque e colaboradores 4 afirmam que as comunidades utilizam as plantas medicinais por serem o único recurso disponível. Outra razão para o uso de plantas medicinais em vez de medicamentos tradicionais é o seu baixo custo 5 .…”
Section: Os Mesmos Achados Corroboram Os Dados Obtidos Com Os Estudos...unclassified
“…Nesse sentido, destaca-se a definição de Oliveira 5 , a fim de fornecer conhecimento sobre as plantas, ele apontou que é benéfico estudar a inter-relação direta entre os seres humanos e o ambiente vegetal, porque a tradição de um povo diz muito sobre a maneira como eles cuidam das espécies vegetais. Assim, ao se constatar que as plantas medicinais interagem significativamente…”
Section: Introductionunclassified